Abraham Lincoln : a life. Vol. 1 - Burlingame, Michael, 1941- (Baltimore : Johns Hopkins University Press, 2012)
In the first multi-volume biography of Abraham Lincoln to be published in decades, Lincoln scholar Michael Burlingame offers a fresh look at the life of one of America's greatest presidents. Incorporating the field notes of earlier biographers, along with decades of research in multiple manuscript archives and long-neglected newspapers, this remarkable work will both alter and reinforce our current understanding of America's sixteenth president. Volume 1 covers Lincoln's early childhood, his experiences as a farm boy in Indiana and Illinois, his legal training, and the political ambition that led to a term in Congress in the 1840s.
Includes bibliographical references and indexes.
eBooks on EBSCOhost
Keywords: Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865; Presidents -- United States -- Biography; Presidents; United States; Biographies